O efeito mediador da atitude financeira na relação da frugalidade e do materialismo no comportamento financeiro e bem-estar financeiro - Vargas, Giovanna Buzanello de (2022)
Financial behavior is associated with the way in which individuals relate to their money. Financial behavior can be affected by individual characteristics, such as frugality and materialism. In addition, individuals who have a good financial attitude as a personal characteristic tend to have better financial behavior. Based on these assumptions, the present research aims to analyze the mediating effect of financial attitude in the relationship of frugality and materialism with financial behavior and, consequently, on financial well-being. Therefore, a survey was carried out with 275 individuals. The data were analyzed using the set of techniques of Modeling Structural Equations of Partial Least Squares (PLS-MEE) and for the test seven proposed hypotheses were carried out. The results showed that the financial attitude presents a total mediation in the relationship between materialism and financial behavior and partial mediation in the relationship between frugality and financial behavior. Furthermore, financial behavior has a positive effect on financial well-being. The results of this study provide a reflection on the relevance of individual financial well-being, as well as the encouragement of financial education, as well as the mediating role of the financial attitude.